New flexible endoscopic controlled stapler technique for the treatment of Zenker's diverticulum. (December 2015) - Faiss, Siegbert; Falck, Stephan; Cordruwisch, Wolfgang; Oldhafer, Karl-Jürgen; Baumbach, Robert
Abstract Objective. Zenker´s diverticulum (ZD) is a rare cause of dysphagia. Various surgical and flexible endoscopic therapies are available with either higher morbidity or either higher recurrence rate. Therefore, improved treatment options are needed. Material and methods. This case report involves an 83-year-old female patient with symptomatic ZD. Under flexible endoscopic control, a new 5 mm fully rotatable surgical stapler was used for the dissection of the septum between the ZD and the esophageal lumen. An ultrathin endoscope and the 5 mm stapler were introduced together through a flexible overtube under conscious sedation. Results. ZD treatment with this new stapler technique was feasible and effective in our patient. Procedure time was 10 min. Clinical symptoms improved immediately and the patient could be discharged the day after the procedure. Conclusion. The described stapler technique under flexible endoscopic control is the first report of this new treatment option for ZD. This new technique under conscious sedation may have some potential advantages compared to standard techniques such as better long-term results and lower complication rates. Further studies are needed.